Developing Tat Twam Asi-based Digital Storytelling Media to Improve English Literacy of VIII Grade Students of Junior High School - Susila, I Komang Dedik; Juliari, I Gusti Ayu Indah Triana; Arshinta, Komang Novi; Arshanti, Kadek Devi (Universitas Pendidikan Ganesha, 2024)
Literacy has continuously become an issue in the education context especially in Merdeka Belajar. This research aims at developing a digital storytelling media “Tat Twam Asi” for VIII Grade Students of Junior High Schools. This research is Research and Development (R&D) using the ADDIE Model consisting analyze, design, develop, implement, and evaluate. The data were collected from observation, interview, and test. The instruments of data collection are field notes, an interview guide, a validation sheet, a questionnaire, and a literacy test. The finding shows that digital storytelling media “Tat Twam Asi” was conducted using ADDIE model. The average percentage of product practicality from teacher responses was 95.1%. Referring to the product practicality percentage criteria, it is known that the practicality level of digital storytelling learning media “Tat Twam Asi” is in the very practical category. Furthermore, the implementation of this media can be considered effective since there was a significant improvement in students’ literacy of VIII Grade students of Junior High School.